2018
DOI: 10.3748/wjg.v24.i16.1708
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring hepatitis B virus reverse transcriptase mutations related to potential antiviral drug resistance and liver disease progression

Abstract: The annual number of deaths caused by hepatitis B virus (HBV)-related disease, including cirrhosis and hepatocellular carcinoma (HCC), is estimated as 887000. The reported prevalence of HBV reverse transcriptase (RT) mutation prior to treatment is varied and the impact of preexisting mutations on the treatment of naïve patients remains controversial, and primarily depends on geographic factors, HBV genotypes, HBeAg serostatus, HBV viral loads, disease progression, intergenotypic recombination and co-infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 127 publications
(234 reference statements)
3
58
0
Order By: Relevance
“…Some RT mutations, such as rtI91L, have been positively associated with HCC; however, this has not been experimentally confirmed in vitro and is considered a putative nucleotide analogues-resistant mutation. These mutations have been reported in Bangladesh as well [25,48].…”
Section: Discussionmentioning
confidence: 74%
“…Some RT mutations, such as rtI91L, have been positively associated with HCC; however, this has not been experimentally confirmed in vitro and is considered a putative nucleotide analogues-resistant mutation. These mutations have been reported in Bangladesh as well [25,48].…”
Section: Discussionmentioning
confidence: 74%
“…Studies have shown that HBV gene resistance mutations are associated with infected HBV genotypes [8,10]. Some scholars believe that HBV C genotype is more prevalent resistant than B genotype [11,12], but some scholars have found that A181T/V mutation, ETV resistance mutation and multidrug resistance mutation is more predominant in C genotype than B genotype, The incidence of M204I and N236T mutation in B genotypes was higher than that of in C genotype [13]. Some scholars believe that the treatment responses of NAs are similar in each genotype, but there are differences among the primary resistance mutations [14].…”
Section: Discussionmentioning
confidence: 99%
“…BN constructed using these sites was shown to detect RR or SR with high accuracy (CA = 98.8%), while achieving the expected accuracy (CA = 53.4%) on randomlabeled data. It is interesting that among the selected 22 sites, 6 located at the RT positions 82, 139, 153, 191, 223 and 233 have been reported as related to drug resistance [31][32][33] . Thus, the findings of groups rather than individual Protein 3D-structure mapping.…”
Section: Sr/rr-associated Mutationsmentioning
confidence: 99%